Analysis of Banking Strategy in Sharia MSME Financing to Improve Bank Health (Case Study of Bank BJB Medan) - Mahvi, Muhammad Rizky; Syarvina, Wahyu; Harahap, Rahmat Daim (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study analyzes the financing strategy of sharia Micro, Small, and Medium Enterprises (MSMEs) implemented by Bank BJB Medan in order to improve the health of the bank. MSMEs have a crucial role in the Indonesian economy, but access to sharia financing is still limited. Bank BJB Medan uses various sharia-based financing schemes, such as musyarakah and mudharabah, to support the growth of MSMEs without an interest system. The research method used is a qualitative approach with interviews, observation, and data analysis techniques. The results of the study show that the sharia MSME financing strategy implemented by Bank BJB Medan is able to reduce financial inclusion, with a Non-Performing Financing (NPF) ratio above 5%. Challenges such as the low understanding of MSME actors towards sharia financing, competition with conventional banks, and the need for investment in digital infrastructure are still obstacles that need to be overcome. Therefore, further innovation is needed in product development, financial education, and digital system optimization so that sharia financing is more inclusive and sustainable .